Situation Report: Hungary, 26 May 1982 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. A Generation of Mistrust - Problems with Working Class Youth Sociography: The Problems of a Critical Genre Academy of Sciences Backs Expansion of Economic Reform The Socialist Countries' Growing Interest in Hungarian Farming